Aquaculture Decision Support Tool: Dashboard Visualisation Viewer - Win, Shelly; Buisson, Marie-Charlotte; Moet, Palal; Soe, Khin; de Silva, Sanjiv; Akester, Michael; Dubois, Mark (International Water Management Institute, 2024)
The new Aquaculture Decision Support Tool (Aqua-DST) will facilitate informed decision-making for aquaculture expansion in the Upper Ayeyarwady River Basin of Myanmar. This includes the Kachin, Magway, Mandalay, Sagaing and Southern and Eastern Shan states/regions. The tool currently covers 37 townships in Myanmar. It incorporates multi-criteria assessments of climate hazards, aquaculture systems, biophysical conditions and socioeconomic factors.